Examining the potential of digital flashcards to facilitate independent grammar learning. (November 2020) - Serfaty, Jonathan; Serrano, Raquel
Abstract: Digital flashcards are widely used and studied for vocabulary, but no previous research has examined this tool for grammar learning. This paper addresses this gap by asking whether full-sentence flashcard training could cause learners to notice and accurately use grammatical patterns. The participants ( N  = 31), school-aged independent English learners in rural Cambodia, underwent 8 sessions of typing translations from their first language, Khmer, to English using the smartphone app Cram.com Flashcards, with items disappearing only when answered without errors. Their performance on trained and untrained items was assessed before treatment, immediately after treatment, and 2 and 18 weeks after treatment. Before the final delayed post-test, one group ( N  = 14) underwent a single refresher session in order to observe its effects on retention. Results showed high gains for all participants (M = 82%) and minimal losses at the second delayed post-test. Equal gains between trained and untrained items demonstrated that participants had indeed inferred grammar rules from the training, and the refresher fully mitigated losses. Further research into digital flashcards for grammar is recommended, to ascertain which factors determine success. Highlights: Digital flashcards can be used to significantly improve grammatical accuracy. Repeated retrieval attempts with feedback on incorrect responses ensures noticing. Ensuring noticing of forms with output leads to high gains and long term retention. Mobile apps promote independent language learning, also in low-resource settings.